Juridical Assessment of Food Safety in Packaged Processed Food Product - Bagus Pambudi, Dwi; Ekawati, Rany (KnE Life Sciences, 2021)
Food safety is one of WHO’s primary concerns during a pandemic. The current Covid-19 pandemic requires us to boost our immune system by eating a healthy and balanced diet. Food consumed by the masses must be free of chemical and biological substances that can be harmful for the body. Nowadays, food products have developed to be more innovative, such as packaged processed food products that can be stored for a long time, generally using Food Additives. The safety of packaged processed food products must be guaranteed by the manufacturers in order to guarantee consumer protection. To ensure this, the government has established the Consumer Protection Law; the Government Regulation on Food Safety, Quality and Nutrition; and the Food and Drug Administration Division. Through the BPOM, the government supervises food products circulating in the community. The supervision carried out by BPOM are preventive and repressive. One form of supervision carried out by BPOM is granting distribution permits for packaged processed food products before they are distributed to the public. Keywords: packaged processed food products, BPOM